Beyond technological relatedness: An evolutionary pro‐growth coalition and industrial transformation in Kunshan, China. (29th September 2021) - Wang, Cassandra C.; Gereffi, Gary; Liu, Zhigao
Abstract: The article develops an analytical framework for an adaptable and evolutionary pro‐growth coalition led by local government to understand regional industrial transformation in developing China. Taking Kunshan as an example, we argue that evolutionary and adaptable coalitions were key to Kunshan's successful transformation from an agriculture county to an export‐oriented industrial center, and to a more diversified city. The coalition of the local state with land‐holding farmers, domestic and international firms, and the central government during the 1980s‐1990s laid a foundation for industrial transformation; the strong coalition of local state and Taiwanese investors in the 1990s‐2000s shaped its new industry of IT manufacturing; and the coalition of local state with multiple actors at various geographical scales contributed a more diversified and innovative industrial structure of Kunshan. This study highlights that industrial evolution is not only driven by technological relatedness but also by the evolutionary state‐led coalition of multiple actors from different levels and at different stages, and appeals for a political economy perspective to understand industrial transformation of resource‐ scarce regions.